Comparison of The Imposition of The Doctrine of Piercing The Corporate Veil in a Limited Liability Company Between The Board of Directors and Shareholders in Terms of Law Number 40 Of 2007 Concerning Limited Liability Company - Ananda, Fauzan Rahmat; Widyawati, Sri (Faculty of Law, Universitas Pekalongan, 2024)
The purpose of writing this journal is to determine the comparison of the imposition of the doctrine of piercing the corporate veil in a Limited Liability Company between the Board of Directors and shareholders, with a review of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). The Doctrine of Piercing the Corporate Veil is a doctrine that has long been present in the business world, especially attached to the legal entity of Limited Liability Companies in Indonesia. UUPT as the law governing Limited Liability Companies in Indonesia has set out the rules regarding the doctrine of piercing the corporate veil. The doctrine has historically been widely used in court decisions, the presence of the doctrine of piercing the corporate veil can penetrate the distinctive nature of a Limited Liability Company, namely limited liability. Departing from this inevitability, the author then formulates the problem in writing this journal, namely why there is a doctrine of piercing the corporate veil in a Limited Liability Company and how the comparison of the imposition of the doctrine of Piercing the Corporate Veil in a Limited Liability Company between the Board of Directors and shareholders is reviewed from the Company Law. The research method used is normative legal research, based on sources obtained through literature studies, in the form of primary, secondary, and tertiary legal materials related to the writing of this journal. This research shows that the presence of the doctrine of piercing the corporate veil in a Limited Liability Company is needed as a form of legal protection for the Limited Liability Company entity and its related parties, and there are differences in the imposition of the doctrine on the Board of Directors of the company and the company's shareholders. The difference in the imposition between the Board of Directors and the shareholders of the company is that, if the Board of Directors is required another article in relation to its good faith in running the company (fiduciary duty), while the shareholders of the company are expressly regulated in Article 3 of the Company Law.